The role of the endogenous opioid system in thermoregulation during exercise - Schwellnus, Martin Peter (MRC/UCT RU for Exercise and Sport Medicine, 2018)
In man the metabolic heat produced during physical exercise stresses the thermoregulatory system, particularly if hot, humid environmental conditions prevail. It has recently been postulated that endogenous opioids may play a role in regulating body temperature at rest and because it has also been shown that blood levels of these substances increase during exercise, the possibility exists that endogenous opioids may play a role in thermoregulation during exercise. A study was conducted in two parts to determine the thermoregulatory response during exercise with and without pharmacologic blockade of the opioid receptor. In Part I nine healthy male subjects performed 30 minutes cycling at 50 % maximal aerobic capacity in an environmentally controlled laboratory. The subjects received either placebo, 2mg or 10mg naloxone hydrochloride in a randomized double-blind crossover fashion prior to the exercise test. Rectal temperatures were recorded at one-minute intervals and cardiorespiratory parameters were measured during the test. Water loss was calculated from differences in nude body weight. In part II eight male subjects performed a graded maximal cycle ergometer test after receiving either placebo or 2mg naloxone in a randomized double-blind crossover fashion. Rectal and sublingual temperatures were recorded before and after the test and oesophageal temperature was recorded at one-minute intervals during the test. Cardiorespiratory parameters were recorded during the test. The results of Part I show that rises in rectal temperature as well as calculated water losses were similar for placebo and after the administration of both 2mg and 10mg naloxone. Similarly, during maximal exercise (Part II) the rise in rectal and oesophageal temperatures was equivalent for placebo and 2mg naloxone but sublingual temperature failed to rise during exercise following the 2mg naloxone dose. Cardiorespiratory responses did not differ between placebo and naloxone tests in both Part I and Part II of the study. These results indicate that naloxone-mediated blockade of opioid receptors does not affect rectal and oesophageal temperature responses to either submaximal or maximal exercise. Naloxone appears to selectively alter the sublingual temperature response to exercise possibly by altering local blood flow. It is concluded that insofar as naloxone induced opioid receptor blockade provides a measure of the function of the endogenous opioid system, this study suggests that the endogenous opioid system does not play a significant role in thermoregulation during exercise.